Co-citation Analysis on Popular References Regarding Cross-Border Tourism - Salouw, Elvis; Setiawan, Bakti; Sarwadi, Ahmad (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Cross-border tourism (CBT) is a new discourse that attracts the attention of researchers from various scientific fields. Along with the development of CBT research, it is necessary to map and trace references related to CBT so that it becomes a reference in research. To that end, using bibliometric analysis by analyzing 334 articles, the study aimed to answer the question; Who is the most influential author in the CBT study? What are the most cited references in studies on CBT? In the Scopus database, what are the most cited journals? Specifically, the study used co-citation analysis to map important references, as well as journals that have a broad influence on CBT topics. Data visualization in this study used VOSViewers as well as content analysis of several related documents. The results of the study showed that the most widely used reference in publications related to CBT is D. J. Timothy's book. The study also emphasizes that Timothy is the most popular author in the discourse on CBT. In addition, in CBT publications, the most influential journal is Tourism Management. This study has implications for researchers who want to conduct studies on CBT in determining references and determining destination journals.